Value of serum LncRNA KIF9-AS1 combined with CT signs in the diagnosis of benign and malignant early pulmonary nodules and its correlation with prognosis - Huichao Wu; Jian Liu; Zhongjun Jing; Zihua Qi; Xianjun Ma; Junying Zhao; Laichong Huang (Journal of Cardiothoracic Surgery)
Abstract Background Early screening for lung cancer and early treatment of malignant pulmonary nodules (PNs) contribute a lot to reducing lung cancer mortality. Whether the highly expressed lncRNA KIF9-AS1 in multiple malignancies is associated with the development of malignant PNs is not clear. This study focused on the diagnosis and prognosis value of KIF9-AS1 in PNs patients. Methods The study population included 101 individuals with benign PNs and 172 patients diagnosed with malignant PNs. The expression of KIF9-AS1 was analyzed by qRT-PCR. The receiver operator characteristic (ROC) curve was plotted to evaluate the diagnostic performance while the Kaplan-Meier curve and multivariate Cox regression analysis were employed for prognosis. Correlation assessment was accomplished by Pearson correlation analysis. Results Differentiated expression of KIF9-AS1 was found in benign and malignant PNs groups. The expression of KIF9-AS1 was positively associated with carcinoembryonic antigen (CEA) and cytokeratin 19 fragments 21 − 1 (CYFRA21-1). KIF9-AS1 presented high accuracy in distinguishing malignant PNs from benign PNs, especially combined with computed tomography (CT). The expression level of KIF9-AS1, and nodule diameter were independent risk factors of poor prognosis. Conclusions Assessment of serum KIF9-AS1 level contributed to clinical diagnosis and prognosis of malignant PNs and also improved the diagnostic value of CT.